Long-term antibody production and viremia in American mink (Neovison vison) challenged with Aleutian mink disease virus - A. Hossain Farid; Irshad Hussain; Priyanka P. Rupasinghe; Jancy Stephen; Irin Arju (BMC Veterinary Research, 2022)
Abstract Background Selecting American mink (Neovison vison) for tolerance to Aleutian mink disease virus (AMDV) has gained popularity in recent years, but data on the outcomes of this activity are scant. The objectives of this study were to determine the long-term changes in viremia, seroconversion and survival in infected mink. Mink were inoculated intranasally with a local isolate of Aleutian mink disease virus (AMDV) over 4 years (n = 1742). The animals had been selected for tolerance to AMDV for more than 20 years (TG100) or were from herds free of AMDV (TG0). The progenies of TG100 and TG0, and their crosses with 25, 50 and 75% tolerance ancestry were also used. Blood samples were collected from each mink up to 14 times until 1211 days post-inoculation (dpi) and were tested for viremia by PCR and for anti-AMDV antibodies by counter-immunoelectrophoresis (CIEP). Viremia and CIEP status were not considered when selecting replacements. Low-performing animals were pelted and the presence of antibodies in their blood and antibody titer were measured by CIEP, and viremia and viral DNA in seven organs (n = 936) were tested by PCR. Results The peak incidences of viremia (66.7%) and seropositivity (93.5%) were at 35 dpi. The incidence of viremia decreased over time while the incidence of seroconversion increased. The least-squares means of the incidence of PCR positive of lymph node (0.743) and spleen (0.656) were significantly greater than those of bone marrow, liver, kidneys, lungs and small intestine (0.194 to 0.342). Differences in tolerant ancestry were significant for every trait measured. Incidences of viremia over time, terminal viremia, seropositivity over time, AMDV DNA in organs and antibody titer were highest in the susceptible groups (TG0 or TG25) and lowest in the tolerant groups (TG100 or TG75). Conclusion Previous history of selection for tolerance resulted in mink with reduced viral replication and antibody titer. Viremia had a negative effect and antibody production had a positive effect on survival and productivity.